Impact of Business Strategies on Continuous Improvement: A Case Study of Al- Hikma Pharmaceutical Company in Jordan - Al-smadi, Ziad; Alhayaly, Omar (The Arab Journal of Administration, 2021)
The aim of this study was to identify business strategies and their impact on continuous improvement. To achieve the objectives of the study, the impact of business strategies dimensions (Cost Leadership Strategy, Excellence Strategy, and Focus Strategy) in the continuous improvement of Al Hikma pharmaceutical company in Jordan. The study population consists of all managers in the all level (top, middle and lower-level departments) of Al-Hikma pharmaceutical company, an appropriate questionnaire list was designed as a data collection tool through which (170) questionnaires were distributed to all managers at Al Hikma Pharmaceutical Company in Jordan. The number of questionnaires that was valid for analysis was (138) questionnaires only. The analytical descriptive approach was used to describe and analyze the study tool. SPSS was used to analyze the study data such as arithmetic averages, standard deviations, ratios, frequencies, and multiple regressions. The results of the study showed that the level of business strategy in Hikma pharmaceutical company was highly agreeable, as well as the level of continuous improvement that emerged with high evaluation and positive impact of the dimensions of business strategies in continuous improvement. The cost-effective driving strategy has been the most effective in the continuous improvement of the Hikma pharmaceutical company in Jordan. The researchers recommended that the management of the company have to adopt a special philosophy in the promotion of business strategies, and the company management have to embrace a business strategies philosophy that must be consistent with the effects of radical changes in the industry and its improvement. And the company must invest its resources after reviewing its cost strategies continuously